Evaluation of the Water Treatment Technology for the Removal of Malathion: Endocrine Disruptor Chemical - Sethi, Pansy (My University, 2011)
Endocrine disruptor chemicals have become major concern to the public, as they impair hormonal functioning and leads to innumerable adverse effects on humans and wildlife. Endocrine distruptor chemicals include plasticizers, metals, food antioxidants and pesticides. Malathion is one of the most potent pesticide which is known to produce adverse effects on human health. Although, malathion has amazing benefits on crops but its regular usage is leading to problems including surface water pollution. Thus, the removal of such EDCs from water has become a necessity. The conventional water treatment processes may be inadequate for reducing certain EDCs as they present great diversity of structural and chemical properties. In the present study, coagulation and flocculation process has been evaluated for the removal of malathion from water. Conventional jar test was employed, by taking different malathion concentration (0 ppm-10 ppm), varying turbidity groups (10-300 NTU), different coagulant dose (25 mg//L-200 mg/L) and flocculant dose (10-30mg/ml) at different contact times of 30 min, 60 min and 90 min. Although, significant reduction of malathion (78%) was observed at 100mg/L of coagulant dose at low turbidity levels at 90 min. But it was found that higher concentrations of malathion could not be removed below the permissible limit at any of the coagulant and flocculant dose. In the case of flocculants 30 mg/ml was the appropriate dose found for the malathion removal. Overall the result of the current study suggests that conventional coagulation/flocculation processes need further improvement and optimisation to remove malathion from water. .Keywords: Endocrine disruptor chemicals, malathion, coagulation, flocculation, Jar test.
M.Sc. (DBTES)
Keywords: Endocrine disruptor chemicals; Malathion; Coagulation; Flocculation; Jar test